PEMBERDAYAAN MASYARAKAT MELALUI OPTIMALISASI PERAN SESEPUH ADAT DALAM PENYELESAIAN SENGKETA DI MASYARAKAT DESA PULAU RAJAK BANYUASIN - Fatria Khairo; Firman Freaddy Busroh (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study aims to analyze community empowerment strategies through the optimization of the role of traditional elders in the dispute resolution system in Pulau Rajak Village, Banyuasin. Amid the strong trend toward legal formalization, traditional institutions are often viewed as marginal, yet sociologically they remain a key pillar of village stability. Using an empirical legal research method, data were collected through in-depth interviews, participatory observation, and literature review. The results indicate that traditional elders in Pulau Rajak Village effectively serve as mediators by applying restorative principles of local wisdom. Community empowerment is achieved through the strengthening of local autonomy in independently resolving internal conflicts. This study recommends the integration of customary rulings into village administration, as well as the need for a formal legal framework at the regional level to strengthen the position of customary institutions without undermining their cultural essence.